An analysis of positional generic and individualized speed thresholds within the most demanding phases of match play in the English Premier League - Kavanagh, R.; McDaid, K.; Rhodes, D.; McDonnell, J.; Oliveira, R.; Morgans, R. (International Journal of Sports Physiology and Performance, 2023)
Objectives To analyze the positional distances covered above generic and individualized speed thresholds within the most demanding phases of match play. Categorized by position, 17 English Premier League players` match data were analyzed over 2 consecutive seasons (2019-20 and 2020-21). The most demanding phases of play were determined using a rolling average across 4 periods of 1, 3, 5, and 10 minutes. Distance covered in the time above the standard speed of 5.5 m/s was analyzed, with individualized metrics based on the maximal aerobic speed (MAS) test data.